Kontribusi Filsafat Ilmu dalam Penelitian Ilmiah dan Kehidupan Sosial - Imam Subekti; Ahmad Syukri; Badarussyamsi Badarussyamsi; Ahmad Fadhil Rizki (Jurnal Filsafat Indonesia, 2021)
Philosophy of science needs its presence in the midst of the development of science and technology which is marked by the sharpening of scientific specialization. Philosophy of science as a theoretical framework and research method has a relationship with scientific research. Philosophy of science explains the problem of science or science which is the basis for logical assumptions (ethical neutralistic doctrine), the empirical results achieved, and the limits of their abilities. Meanwhile, the research methodology describes efforts to develop science based on the scientific method, which consists of two parts, namely both deductive and inductive.        The contribution of the philosophy of science in scientific research is: As a basis for the development of science or theory, the philosophy of science as a means of testing scientific theory reasoning. Philosophy of science is able to test, reflect, criticize assumptions and scientific methods in a scientific research. As a foundation in science at the university level. Philosophy of science provides a logical basis for research methodology. The contribution of the philosophy of science in research methodology can also be filling and broadening the cognitive horizons (reason) of what is called science, which is expected to create understanding for the discipline in scientific work, as well as increase the motivation of a researcher to carry out tasks seriously.  Writing this article uses a qualitative approach by using library research, namely by examining reading sources that have to do with the study being discussed.